Pengaruh Stres Kerja Terhadap Kepuasaan Kerja Karyawan Pada PT. Sri Rejeki Isman Textile Sukoharjo - Kartikawati, Dina, Drs. Anton Agus Setyawan, SE., M.Si (2016)
The purpose of this research is to analyze the effect of work stress on job satisfaction of employees at PT. Sri Rejeki Isman Textile Sukoharjo. The study population was all employees of PT. Sri Rejeki Isman Textile Sukoharjo , a sample is taken 100 employees at PT. Sri Rejeki Isman Textile Sukoharjo, the sampling technique using simple random sampling. The data analysis method used : (1) test the research instrument , namely the validity and reliability, (2) simple linear regression, (3) Test the hypothesis, that the t test , F test and the coefficient of determination R Square . It can be concluded that, job stress and significant negative effect on employee job satisfaction. Variable employee satisfaction can be explained by the variable job stress by 11.8 % and the remaining 88.2 %, so there are many factors that affect laiinya lower employee job satisfaction